Pemulihan Ekonomi Pasca Kerusuhan Tahun 1998 (Studi KasusKota Surakarta) - Djoko Santoso (Unisia, 2008)
Economically, after the social unrest in 1998, Surakarta City has been well-known as anunlivable city. No investors are interested to invest, unless otherwise the condition changes.This research article tries to explore economic policies by Surakarta Government after theriot. Specifically, this article proposes to analyze economic condition of Surakarta Citybefore and after riot; public policies taken by Surakarta government to run economicrecovery; and recovery policies using perspective of economic education. Using qualitativeresearch, this research reveals that, there have been economic significant changes inthree to five years after riot; Surakarta government policies for economic recovery havebeen matched with public policy decision models; and the perspective of economic educationhas been applied effectively to recover Surakarta economic condition.Keywords: policy analysis, economic recovery, economic education perspective.